2010
DOI: 10.1371/journal.pone.0013408
|View full text |Cite
|
Sign up to set email alerts
|

Immune Events Associated with High Level Protection against Schistosoma japonicum Infection in Pigs Immunized with UV-Attenuated Cercariae

Abstract: BackgroundThe vaccination of radiation-attenuated Schistosoma japonicum cercariae can induce effective protection in artiodactyl, but the immune events related to protective immunity are not fully understood. To provide a paradigm for a human recombinant antigen vaccine, we have undertaken a vaccination and challenge experiment in pigs, which was recognized as an appropriate animal model in this type of study because of their similarity to human in immunology, and investigated the relative immune events induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
3
24
1
Order By: Relevance
“…One possible reason is that immune protection against schistosomes is associated with the induction of Th1-biased immune responses [3032]. However, in our study, PD-1 blockade had no effect on Th1 immune responses.…”
Section: Discussioncontrasting
confidence: 69%
“…One possible reason is that immune protection against schistosomes is associated with the induction of Th1-biased immune responses [3032]. However, in our study, PD-1 blockade had no effect on Th1 immune responses.…”
Section: Discussioncontrasting
confidence: 69%
“…In swine, IFN-γ has been shown to be related to IgG2 production [42] which supports the hypothesis that the IgG1:IgG2 ratio could provide a suitable indicator of adaptive immunity potentiation towards a Th1 or Th2 response, as in other species. Interestingly, our results showed that the post-challenge production of CSFV-specific IgG2, but not IgG1, was enhanced in vaccinated as compared to unvaccinated pigs.…”
Section: Discussionsupporting
confidence: 54%
“…With vaccines for schistosomes, the protection obtained with cercariae that have been attenuated with ionizing radiation is considered to be the ‘gold’ standard against which other vaccine candidates are compared for clinical development (McManus & Dalton, 2006; Hotez et al , 2008a; McManus & Loukas, 2008; Loukas et al , 2011). Elevated levels of protection against Schistosoma japonicum can be induced by exposure to X-irradiated cercariae in macaques (Hsu et al , 1969) and cattle (Hsu et al , 1983), by exposure to γ-irradiated cercariae in bovines (Hsu et al , 1984), and UV-attenuated cercariae in pigs (Tian et al , 2010). Vaccine efficacies are variable, however, as exemplified by immunization of mice with γ-irradiated cercariae of S. japonicum, which elicits only modest resistance to reinfection (Zhang et al , 1999).…”
Section: Discussionmentioning
confidence: 99%